Perkawinan Adat Saibatin Dalam Perspektif Hukum Positif Indonesia - Pelangi, Intan; Abunawar, Hadri; Saputra, Rizki Berlian; Pribadi, Adhimaz Kondang (Universitas Muhammadiyah Metro, 2024)
It is not uncommon in the Lampung Saibatin society for husbands and wives to live apart for a certain period after marriage. This can be caused by various factors between them and between their families. However, this does not mean that their marriage is not approved, but rather that there are certain conditions that have not yet allowed them to live together. Considering the above background, the writer is interested in formulating the following problems: is the marriage carried out according to Lampung Saibatin customs valid under the prevailing marriage laws?; what are the backgrounds that lead to marriage according to Lampung Saibatin customs?. The research used in the preparation of this work is empirical legal research. The data obtained by the writer is qualitative data which will be examined using the constant comparative analysis method, namely by comparing and developing empirical research with related legislation. A marriage with an agreement to live apart temporarily is valid if the conditions and pillars of marriage are met. Concerning the fulfillment of the rights and obligations of husband and wife, it also becomes a non-issue if both parties have agreed to the temporary non-fulfillment of rights and the non-implementation of obligations. The agreement to live apart temporarily is made for several reasons and is not something new for the community of Belalau District, West Lampung Regency